Generalized weakly demicompact and S-demicompact linear relations and their spectral properties - Fakhfakh, Majed; Jeribi, Aref (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.9 We extend the concept of generalized weakly demicompact and relatively weakly demicompact operators on linear relations and present some outstanding results. Moreover, we address the theory of Fredholm and upper semi-Fredholm relations attempting to establish a connection with them.